Antidepressants on Multiple Sclerosis: A Review of In Vitro and In Vivo Models - Stamoula, Eleni; Siafis, Spyridon; Dardalas, Ioannis; Ainatzoglou, Alexandra; Matsas, Alkis; Athanasiadis, Theodoros; Sardeli, Chrysanthi; Stamoulas, Konstantinos; Papazisis, Georgios (Frontiers in Immunology, 2021)
Background: Increased prevalence of depression has been observed among patients with multiple sclerosis (MS) and correlated with the elevated levels of proinflammatory cytokines and the overall deregulation of monoaminergic neurotransmitters that these patients exhibit. Antidepressants have proved effective not only in treating depression comorbid to MS, but also in alleviating numerous MS symptoms and even minimizing stress-related relapses. Therefore, these agents could prospectively prove beneficial as a complementary MS therapy. Objective: This review aims at illustrating the underlying mechanisms involved in the beneficial clinical effects of antidepressants observed in MS patients. Methods: Through a literature search we screened and comparatively assessed papers on the effects of antidepressant use both in vitro and in vivo MS models, taking into account a number of inclusion and exclusion criteria. Results: In vitro studies indicated that antidepressants promote neural and glial cell viability and differentiation, reduce proinflammatory cytokines and exert neuroprotective activity by eliminating axonal loss. In vivo studies confirmed that antidepressants delayed disease onset and alleviated symptoms in animal models of MS. Further, antidepressant agents suppressed inflammation and restrained demyelination, by decreasing immune cell infiltration of the CNS. Conclusion: Antidepressants were efficient in tackling numerous aspects of disease pathophysiology both in vitro and in vivo models. Given that several antidepressants have already proved effective in clinical trials on MS patients, the inclusion of such agents in the therapeutic arsenal of MS should be seriously considered, following an individualized approach to minimize the adverse events of antidepressants in MS patients.